Measuring depression and anxiety prevalence among Iraqi healthcare college students using hospital anxiety and depression scale - Sarmed H. Kathem; Ali A. Al Jumaili; Malak Noor-Aldeen; Noor Najah; Dema Ali Khalid (Centro de Investigaciones y Publicaciones Farmaceuticas, 2021)
Objective: The study aimed to 1) measure the prevalence of depression and anxiety among Iraqi pharmacy and medical students at a number of universities in Baghdad using Hospital Anxiety and Depression Scale (HADS) and 2) investigate the association between various sociodemographic factors and students' HADS scores. Methods: This study was based on a cross-sectional descriptive design in four universities in Baghdad, Iraq. Depression and anxiety were screened using an Arabic version of the HADS. An online survey was administered via Qualtrics to convenience samples of students at four colleges of pharmacy and a college of medicine between March and June 2018. Multiple linear regression was used to identify factors associated with depression and anxiety symptoms among the participants. Results: The researchers received 750 usable surveys. The participating students spent more time browsing social media (6.64 hours/day) than studying (1.92 hours/day) and exercising (2.83 hours/week). Approximately forty-six percent (45.9%) of the participants had scores that indicated depression symptoms and one-quarter (24.8%) had scores that indicated depression borderline symptoms. More than one-half (52.1%) of the participants had scores that indicated anxiety symptoms, while 20.1% had scores that indicated anxiety borderline symptoms. According to the multiple linear regression analysis, more depression and anxiety symptoms were significantly (p-value <0.05) associated with higher study hours weekly and lower sleep hours at night, academic achievement, and colleagues and family social support during exams. Conclusions: Pharmacy and medical students may be vulnerable to depression and anxiety because of long study hours.. To reduce their levels of anxiety and depression, they may need more social support, more exercise, more sleep, less social media use and a lower academic workload.